Enumeration rules and numeracy problems in tourism activities - Aan Putra; Zulkardi Zulkardi; Ratu Ilma Indra Putri; Laswadi Laswadi (Journal of Honai Math, 2025)
School mathematics is designed to equip students with foundational mathematical knowledge while simultaneously fostering mathematical literacy, including numeracy, essential for effective problem-solving. Achieving these objectives requires students to engage with mathematics through contexts that are relevant to their prior knowledge and lived experiences, thereby facilitating a more meaningful mastery of mathematical concepts and literacies. The tourism sector offers a rich context for such engagement, presenting opportunities to connect enumeration rules and numeracy with real-world scenarios. This study investigates the integration of enumeration rules and numeracy through tourism-based learning activities situated in Kerinci, Jambi. The aim is to inform the development of learning resources that are locally relevant and reflect the authentic experiences of students. Employing an exploratory qualitative methodology, this research involved field observations and semi-structured interviews with local tourism practitioners and mathematics educators. Thematic analysis was conducted to identify genuine tourism-related activities in Kerinci that illustrate the application of enumeration principles and numeracy skills. Findings indicate that a range of tourism activities including selecting transportation modes, accommodations, destinations, travel routes, and tourist attractions are inherently linked to enumeration (determining the number of possible choices) and numeracy (applying quantitative reasoning to make optimal decisions). By situating enumeration and numeracy within everyday tourism practices, this study demonstrates how local contexts can enhance mathematics instruction. The results provide a foundation for future design research focused on developing and evaluating instructional trajectories that incorporate local tourism scenarios into mathematics teaching, particularly regarding enumeration and numeracy concepts.